A DEVELOPING INTERCULTURAL COMPETENCE OF STUDENTS IN FOREIGN LANGUAGE CLASSROOM: DEVELOPING INTERCULTURAL COMPETENCE OF STUDENTS IN FOREIGN LANGUAGE CLASSROOM - Norbekova, Ra’no (Журнал иностранных языков и лингвистики, 2022)
European and Uzbekistan higher education operates in a new environment characterized by globalization, new communicative technologies, increased competition and commercialization, English being the language of international communication. Hence, the importance of learning foreign languages and their role in the labor market as a whole has increased and is leading to a higher motivation in the study of foreign languages.